2013
DOI: 10.1074/jbc.m112.417246
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the Ca2+-sensing Stromal Interaction Molecule STIM1 Regulate Ca2+ Influx by Altered Oligomerization of STIM1 and by Destabilization of the Ca2+ Channel Orai1

Abstract: Background: Calcium influx (I CRAC ) is important for proper cell function. Results: A novel STIM1 mutant increases I CRAC , Ca 2ϩ -dependently destabilizes Orai1, and alters clustering. A new mathematical model explains the phenotype. Conclusion: The molecular kinetics of STIM1 and Orai1 are major determinants of I CRAC . Significance: The diffusion trap model and alteration of Orai1 stability provide a tool for understanding I CRAC regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
71
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 38 publications
15
71
0
Order By: Relevance
“…6E). Similar results were obtained by Kilch et al (Kilch et al, 2013) and by Hoover and Lewis, who elegantly correlated the stoichiometry of STIM1:Orai1 within STIM1-Orai1 puncta at the plasma membrane with SOCE levels (Hoover and Lewis, 2011). They showed that Orai1 trapping within STIM1 puncta at the plasma membrane requires one or two STIM1 molecules to bind to the presumed Orai1 tetramer (a Orai1:STIM1 stoichiometry of 4:2); however, this trapping is not sufficient to open Orai1 as maximal SOCE activity is achieved at an Orai1: STIM1 stoichiometry of 1:2 within puncta at the plasma membrane (Hoover and Lewis, 2011).…”
Section: Specificity Insupporting
confidence: 81%
“…6E). Similar results were obtained by Kilch et al (Kilch et al, 2013) and by Hoover and Lewis, who elegantly correlated the stoichiometry of STIM1:Orai1 within STIM1-Orai1 puncta at the plasma membrane with SOCE levels (Hoover and Lewis, 2011). They showed that Orai1 trapping within STIM1 puncta at the plasma membrane requires one or two STIM1 molecules to bind to the presumed Orai1 tetramer (a Orai1:STIM1 stoichiometry of 4:2); however, this trapping is not sufficient to open Orai1 as maximal SOCE activity is achieved at an Orai1: STIM1 stoichiometry of 1:2 within puncta at the plasma membrane (Hoover and Lewis, 2011).…”
Section: Specificity Insupporting
confidence: 81%
“…However, when ER Ca 2ϩ was depleted with thapsigargin, the recovery of STIM1 decreased significantly by ϳ50% postbleaching, indicating that STIM1 became less mobile (Fig. 5, B and C), in agreement with previous reports (20,26). We then repeated this protocol on cells pretreated with E2.…”
Section: Stim1 Mobility Within the Er Issupporting
confidence: 76%
“…It is well described that the STIM1 to Orai1 ratio highly influences their activity. Some reports proposed that a ratio of 2/1 STIM1/Orai1 is optimal for maximal SOCE activity (52,53). Thus, Orai1 overexpression alone may "dilute" the STIM1 binding to individual Orai1 channels, which could explain our data.…”
Section: Discussionsupporting
confidence: 65%